Differentiating Chondroitin Sulfate Glycosaminoglycans Using Collision-Induced Dissociation; Uronic Acid Cross-Ring Diagnostic Fragments in a Single Stage of Tandem Mass Spectrometry. Issue 3 (June 2015) - Kailemia, Muchena J.; Patel, Anish B.; Johnson, Dane T.; Li, Lingyun; Linhardt, Robert J.; Amster, I. Jonathan
The stereochemistry of the hexuronic acid residues of the structure of glycosaminoglycans (GAGs) is a key feature that affects their interactions with proteins and other biological functions. Electron-based tandem mass spectrometry methods, in particular electron detachment dissociation (EDD), have been able to distinguish glucuronic acid (GlcA) from iduronic acid (IdoA) residues in some heparan sulfate tetrasaccharides by producing epimer-specific fragments. Similarly, the relative abundance of glycosidic fragment ions produced by collision-induced dissociation (CID) or EDD has been shown to correlate with the type of hexuronic acid present in chondroitin sulfate GAGs. The present work examines the effect of charge state and degree of sodium cationization on the CID fragmentation products that can be used to distinguish GlcA and IdoA containing chondroitin sulfate A and dermatan sulfate chains. The cross-ring fragments 2, 4 A n and 0, 2 X n formed within the hexuronic acid residues are highly preferential for chains containing GlcA, distinguishing it from IdoA. The diagnostic capability of the fragments requires the selection of a molecular ion and fragment ions with specific ionization characteristics, namely charge state and number of ionizable protons. The ions with the appropriate characteristics display diagnostic properties for all the chondroitin sulfate and dermatan sulfate chains (degree of polymerization of 4–10) studied.